(3GdfGSN hGdefShNs - (3CMeO Hf eMeO Hf ESeGYjd GdeUQj GdfMhj, CHh LYaQ , GHf GdfMGS, J (B338 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdLdjd CHh GdMSf Ydi Hf EHQGgje Hf SYjO GdMhai bGd CHh LYaQ CHJOF gPG GdcJGH , hgh cJGH GdfGSN hGdefShN HMeO GdGdg GdhGMO GdLHGQ , GdYRjR GdbgGQ s
(3BNQgG (B:s
(3hNU eMeOkG fHi GdQMeI HGdUdGI hGdJSdje Je cJGH GdfGSN hGdefShN ai GdbQBf , hGdMeO ddg cKjQkG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B116s
(3GdfSNI HgG MhGTs
(3YdjgG ebGHdI jQLY JGQjNgG Edi SfI (B737(3g`s
(3Ydi GdeLehYI JedcGJ CbOegG SfI (B1198(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs